Diagnostic Accuracy of the FIGO and the 5-Tier Fetal Heart Rate Classification Systems in the Detection of Neonatal Acidemia - Martí Gamboa, Sabina; Giménez, Olga Redrado; Mancho, Jara Pascual; Moros, María Lapresta; Sada, Julia Ruiz; Mateo, Sergio Castan (American Journal of Perinatology, 2017)
Objective The objective of this study was to determine ability to detect neonatal acidemia and interobserver agreement with the FIGO 3-tier and 5-tier fetal heart rate (FHR) classification systems.Design This was a case–control study.Setting This study was set at the University Medical Center.Population A total of 202 FHR tracings of 102 women who delivered an acidemic fetus (umbilical arterial cord gas pH ≤ 7.10 and BE < − 8) and 100 who delivered a nonacidemic fetus (umbilical arterial cord gas pH > 7.10) were assessed. A subanalysis was performed for those fetuses who suffered severe metabolic acidemia (pH ≤ 7.0 and BE < − 12).Methods Two reviewers blind to clinical and outcome data classified tracings according to the new 3-tier system proposed by the FIGO and the 5-tier system proposed by Parer and Ikeda.Main Outcome Measures Sensitivity and specificity for detecting neonatal acidemia and interobserver agreement in classifying FHR tracings into categories of both systems were studied.Results The 3-tier system showed a greater sensitivity and lower specificity to detect neonatal acidemia (43.6% sensitivity, 82.5% specificity) and severe metabolic acidemia (71.4% sensitivity, 74.0% specificity) compared with the 5-tier system (36.3% sensitivity, 88% specificity and 61.9% sensitivity, 80.1% specificity, respectively). Both systems were compared by area under the receiver-operating characteristic curve, with comparable predictive ability for detecting neonatal acidemia (FIGO—area under the curve [AUC]: 0.63 [95% confidence interval [CI]: 0.57–0.68] and Parer—AUC: 0.62 [95% CI: 0.56–0.67]). Interobserver agreement was moderate for both systems, but performance at each specific category showed a better agreement for the 5-tier system identifying a pathological tracing (orange or red, κ: 0.625 vs. pathological category, κ: 0.538).Conclusion Both systems presented a comparable ability to predict neonatal acidemia, although the 5-tier system showed a better interobserver agreement identifying pathological tracings.
Keywords: electronic fetal monitoring; classification systems; interobserver agreement; cardiotocography